ПСИХОЛОГІЧНА АДАПТАЦІЯ ЯК УМОВА ФОРМУВАННЯ ІННОВАЦІЙНОЇ ОСОБИСТОСТІ УЧНІВ ЗАГАЛЬНООСВІТНЬОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
In the article the author define program to the formation of the innovation personality pupil, open problem anxiety. There are revealed which stopped its development. This article considers the establishment and mould experiments.